SERS‐based biosensor for Alzheimer disease evaluation through the fast analysis of human serum. Issue 3 (1st January 2020) - Carlomagno, Cristiano; Cabinio, Monia; Picciolini, Silvia; Gualerzi, Alice; Baglio, Francesca; Bedoni, Marzia
Abstract: Alzheimer disease (AD) is the most common form of dementia in the elderly, progressively affecting the cognitive functions with a complex diagnostic procedure that limits the time for a prompt intervention. In this study we optimized a reliable protocol for the analysis of AD patients and healthy subjects' serum using the Surface Enhanced Raman Spectroscopy (SERS), taking into consideration the effect of different variables on the final spectra, analyzed and compared through multivariate analysis and correlated with hippocampus volume. As results, we demonstrated a statistical difference between the spectra collected from the two investigated groups, with an accuracy, precision and specificity of respectively 83%, 86%, and 86%. The correlation of these data with those obtained from MRI, demonstrated a direct correlation between Raman spectra and hippocampus degeneration showing the Raman Spectroscopy (RS) as a potential tool for the monitoring of AD progression and rehabilitation treatments. Abstract : Serum collected from patients affected by Alzheimer disease and healthy subjects was analyzed using Surface Enhanced Raman Spectroscopy, identifying statistical differences between the signals collected from the two groups. The results of the statistical analysis were correlated with the patient's total hippocampus volume obtained from Magnetic Resonance Imaging, revealing a direct correlation between Raman data and hippocampus degeneration.